A new non‐expressed allele HLA‐A*03:168N, identified by serological and sequence‐based typing in a voluntary Norwegian hematopoietic stem cell donor. Issue 3 (7th January 2014) - Abad, M. L.; Balas, A.; Andersen, I.; Rodríguez‐Calvo, M. I.; Eiras, A.; Vicario, J. L.
<x xml:space="preserve">Abstract</x> HLA‐A*03:168N differs from HLA‐A*03:01:01 by a single nucleotide substitution resulting in a coding change Y27X.